Kajian Ekologi Sastra dalam Cerita Rakyat Hubula di Kabupaten Jayawijaya Provinsi Papua: Study of Literary Ecology in Hubula Folklore in Jayawijaya, Papua - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Some folktales can be studied through an ecological approach. Based on that reason, the problem discussed in this study is the structure and ecological reality of Hubula in the folklore of the Hubula through ecological approach. The purpose of this research is to explain the structure of the Hubula folklore based on the theory of literary structures and to describe the ecological reality in the folklore of the Hubula tribe through the literary ecological approach. The benefits of this research include practical benefits and scientific (theoretical) benefits. This study uses two theories, namely literary structuralism theory and literary ecological approach. This research is qualitative. The method used in this research is the method of collecting data through field studies; data processing methods through careful reading, identification, and data selection; and data analysis methods through a literary ecological perspective. This research found that the formal structure of the Hubula folklore generally has few characters in the story, the theme of the story is simple, the plot is forward, the setting is in the open, and a single third person perspective. Apart from that, ecological reality is also found in the folklore of Hubula in Jayawijaya Regency. This ecological reality can be seen from the background of the place (the environment) which is still well preserved, the ecology of the forest which is still green and sustainable becomes an ecosystem for other living things besides humans, and there are water sources that are still abundant and clear for the survival of the Hubula.